PROSTHETIC TREATMENT OF PATIENT WITH MANDIBLE RESECTION - Ivan Gerdzhikov (Peytchinski Publishing, 2023)
Background: Literature findings indicate an increase in mandible resection cases. Retention and stability of dentures are the main issues in the prosthetic treatment of these defects. Aim: The aim of the presented clinical case is to explore the possibility of prosthetic treatment of a patient with mandible resection of the frontal area. Materials and methods: The clinical case monitors the prosthetic treatment of a 38-year-old patient with mandible cancer and resection in the frontal zone. The treatment plan was based on taking preliminary alginate impressions and developing gypsum models. It is planned to develop a partial acrylic denture sealed with silicone material. Additional preparation of the gypsum master model in the resection area took place in order to achieve the equal thickness of the special silicone material. The base of the alveolar bone was restored with hard plaster. In addition, the occlusal rim was fabricated with the purpose of establishing the centric relation and occlusal relationship. The denture was fabricated by acrylic resin with a low quantity of residual monomer and adjusted after adding silicone material over the resected part with functional tests to complete the design of the defect area. Results: The accessed treatment results indicate good retention and stability of the denture. The application of silicone material provided a non-traumatic transition of the masticatory pressure without decubital ulcers in the resected zone. Conclusion: The application of appropriate prosthetic treatment methods in patients with mandible resection leads to the successful restoration of feeding and speaking functions.